Advancements in laundry wastewater treatment for reuse: a review. Issue 11 (16th November 2022) - Kumar, Sushil; Mostafazadeh, Ali Khosravanipour; Kumar, Lalit R.; Tyagi, R. D.; Drogui, Patrick; Brien, Emmanuel
Abstract: Laundry related activities produce huge quantity of wastewater that is very rich in lint, dyes, surfactants, and detergents. The large amount of laundry wastewater (LWW) is generated by extensive human activities. LWW needs to be treated in order to tackle the challenging problem of water pollution and to accomplish water sustainability. To achieve this success, LWW can be reused for several purposes such as irrigation, construction activities, vehicle washing etc. However, there are several challenges in the reclamation of LWW like effective handling of the wastewater and meeting the regulatory criteria. Based on the literature review it seems that a single treatment process is not sufficient to treat LWW up to acceptable reuse standards. To that end, different treatment chains have been proposed: i) hybrid processes combining membrane filtration with adsorption; ii) advanced oxidation process using ultraviolet (UV) and hydrogen peroxide (H2 O2 ); iii) coagulation-flocculation combined with sand filtration; iv) combination of ozonation process, adsorption, and ultrafiltration (UF). This review paper discusses the selection of suitable treatment technology depends on several factors: i) a well-designed equipment, ii) cost-effectiveness of treatment method and iii) desired characteristics of the treated water. The review paper also presents solutions for treatment and reclamation of LWW.